The mighty armor : the adventures of Toby Digz - Hernandez, David (Nashville, Tenn. : Tommy Nelson, 2003)
To escape a spooky night in the treehouse, Toby and Tut travel through time and find themselves in a Roman jail cell in 60 A.D. with the apostle Paul, who teaches Toby how to put on the "Armor of God."
Keywords: Paul; Time travel; Courage; Christian life; Adventure and adventurers